Analysis on Queue System at Vitka Point Gas Station Number 14.294.722 on Motorcycle Line with Pertalite-Based Fuel - Bima Wahyu Pratama; Fandy Bestario Harlan; Adhitomo Wirawan; Asadian Puja Enggita (Politeknik Negeri Batam, 2022)
This study aims to find out the performance of the queuing system at SPBU 14.294.722 Vitka Poin, Batam City on Pertalite fuel for motorcycles. The performance of the queuing system was analyzed to whether it has reached the optimal level. The data were collected through interviews and observations. Then, the obtained data were analyzed using a single line queuing system (single-channel, single-phase). The study used quantitative data in which the calculation was assisted by the